The Image Models of PT East Jakarta Industrial Park (EJIP) - Suryati, Lili; Cahyono, Yoyok; Sudarso, Andriasan; Sudaryo, Yoyo; Wardana, Wikrama; Ayu Sofiati (Efi), Nunung; Pertiwi, R. Dewi; Limakrisna, Nandan (International Journal of Advanced Multidisciplinary, 2023)
In an increasingly competitive market, companies are vying to meet customer needs and desires. Consequently, customer satisfaction has become the primary goal of every company. However, PT. EAST JAKARTA INDUSTRIAL PARK is facing a decline in investor shares, indicating that the company's image may need improvement. To this end, this study aims to explore the combined impact of service quality and customer relations on the image of PT. EAST JAKARTA INDUSTRIAL PARK. This implies that these elements of service quality require sustained attention. On the other hand, the tangibles dimension falls under quadrant 2 (focus here), indicating that significant efforts need to be directed towards improving this area as a top priority. PT. EJIP's commitment to fostering strong relationships with its customers is evident in various aspects. These include frequent communication with customers, ensuring product quality, fulfilling agreements with customers, building trust in the company's integrity, reputation, and reliability. Despite competition from other investment vehicles, PT. EJIP strives to retain its customers' loyalty by consistently providing exceptional service and maintaining a reputation as a trustworthy and reliable company. According to the findings of this study, the image of PT. EJIP is jointly impacted by service quality and customer relations. However, a closer analysis reveals that customer relations play a dominant role in shaping the image of the company, while service quality does not have a significant impact. Please refer to Table 4.21 for more details.